MOTIVATIONAL COMPONENT AS A SUCCESS TO ORGANIZE AN INDEPENDENT WORK OF STUDENTS AT THE DEPATMENT OF THERAPEUTIC DENTISTRY - Yu. V. Sidash (Український стоматологічний альманах)
The determining characteristic for understanding the student's educational activity is independence. Understanding the problem of autonomy of students in the educational process is the basis of a responsible attitude to the professional training of future specialists. Reforming higher education causes an increase in interest in finding ofthe effective pedagogical conditions for the formation of students' autonomy which is capable of mastering the content of educational material qualitatively, intentionally planning self-development of intellectual, moral and physical abilities. The introduction of a credit-module training system makes the student's individual work more organized, since each practical lesson is conducted as a micro-module and each student is under the systematic control of the teacher. The results of current and modular control give fora teacher the opportunity to receive prompt educational and didactic measures that will improve the quality of students'at the department of therapeutic dentistry training  aimed for further independent work and develop autonomy in obtaining new knowledge. According to A. Furman, the development of skills of independent work in the conditions of a credit-module system promotes the use in the educational process of problem-modular lectures of three types: scientific information, scientific-designed and ideological-reflexive.Problem-modular lectures are known as an organized communication between a lecturer and an audience, in which there is a coordinated decision to a scientific problem, realization of business, informational and psychological exchange of knowledge, skills and values between students and the teacher.In the scientistsopinion all this is a kind of motivation of educational activityand the basis of interaction development. Other forms of organization of the educational process can be significant for the development of students' organization of educational process: seminars, scientific conferences, disputes, etc. Participation of students is a real opportunity not only to acquire new knowledge and skills, expand experience, but also to determine the level of competence on certain issues, express their own vision and simply to establish themselves in their own self-sufficiency. We determined the independence of students based on the communicative principle proposed by A. Schukin. Communicativeness is manifested by communicatively-motivated behavior of the teacher and student in the course of educational activity, as well as in the objectivity of the communication process which is expressed in the careful selection of linguistic intentions  and thus communication situations that reflect the practical interests and needs of students. Communicativeness is necessary item for a successful and active work with pedagogical information. Such information is aimed at educating and students. Therefore, the teacher's ability to express their opinion is correct, clear and understandable way and this is a guarantee of success in their work. Thus, it is possible to make moreinteresting even the most difficult topic of the class. The process of the study isto create a sincere atmosphere of communication in the audience, establish contact with students, achieve mutual understanding and form a sense of confidence in the student. Verbal assessment of the academic activity of students by the teacher plays a great significance which is one of the most operational forms of evaluation.It is necessary to use various, systematic assessments that should be based on the ideas ofeducative humanization and should also be a point that involves people's attitudes toward each other. Such assessments should include an analysis of learning activities rather than criticism of the student's personality. The above-mentioned conditions for the development of independence in the conditions of a credit-module system together with pedagogical means, forms and methods of teaching provide a developing personality function during educational activities.